2012
DOI: 10.1111/j.1468-1293.2012.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological opportunistic infections and neurological immune reconstitution syndrome: impact of one decade of highly active antiretroviral treatment in a tertiary hospital

Abstract: BackgroundDespite the reported decrease in the incidence and mortality rates of central nervous system (CNS) infections after the introduction of highly active antiretroviral therapy (HAART), few studies have focused on the global incidence and the relationship of these diseases with immune reconstitution inflammatory syndrome (IRIS) in the developed world. MethodsA descriptive cohort study of all consecutive adult HIV-infected patients with CNS opportunistic infections diagnosed between 2000 and 2010 in a ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
0
19
1
4
Order By: Relevance
“…We do not think that our results can be explained by the occurrence of PML-IRIS, even though about 19 % of the PML cases reported in the HAART era are cases of PML-IRIS [32,33]; the radiological findings of the lesions in our cases and their clinical course and onset are not consistent with a diagnosis of PML-IRIS [22,34].…”
Section: Discussioncontrasting
confidence: 78%
“…We do not think that our results can be explained by the occurrence of PML-IRIS, even though about 19 % of the PML cases reported in the HAART era are cases of PML-IRIS [32,33]; the radiological findings of the lesions in our cases and their clinical course and onset are not consistent with a diagnosis of PML-IRIS [22,34].…”
Section: Discussioncontrasting
confidence: 78%
“…However, similar to IRIS, CNS-IRIS often occurs within the context of an OI and therefore the incidence of CNS-IRIS is frequently assessed in populations with a particular OI. Thus the incidence of CNS-IRIS is highly variable, averaging 15-25% and ranging upwards of 40% in high-risk individuals (25-29**). A study of 110 consecutive patients with HIV and a diagnosed CNS OI demonstrated the occurrence of CNS-IRIS to be 16.4% (29**).…”
Section: Incidence Of Iris and Cns-irismentioning
confidence: 99%
“…Thus the incidence of CNS-IRIS is highly variable, averaging 15-25% and ranging upwards of 40% in high-risk individuals (25-29**). A study of 110 consecutive patients with HIV and a diagnosed CNS OI demonstrated the occurrence of CNS-IRIS to be 16.4% (29**). Similarly, a study of 620 patients admitted to hospital with new or worsening neurological disease and HIV demonstrated an overall CNS-IRIS incidence of 11.8% (26); however 40% of patients with CNS tuberculosis in this cohort developed CNS-IRIS.…”
Section: Incidence Of Iris and Cns-irismentioning
confidence: 99%
See 2 more Smart Citations